The Image of Paganism in the Age of Reason: From Idolatry towards a Secular Concept of Polytheism - Horák, Pavel (The pomegranate, 2016)
This article argues that the concept of "paganism," though originally theological in nature, came to be used in the Enlightenment and its secular thought as a term for non-Abrahamic religions. Discussions on paganism were conducted in an environment where concerns about religious plurality had become central. As such, these discussions, and their subject-paganism, also served as a means to find solutions for concerns about religious plurality. This article will focus on three components of the discussion on paganism: (i) the origin of idolatry, (ii) the nature of gods, and (iii) the nature of pagan worship. This article argues that purportedly secular concerns regarding paganism expressed by Deist and Enlightenment scholars were in fact rooted in Christian theology. This article is divided into four sections. The first section gives a general account of relevant discussions taking place in the seventeenth century. The second section discusses the father of English deism, Herbert of Cherbury, and his notion of paganism. The third section discusses Herbert's successors. The fourth section discusses David Hume and his work on paganism. The article argues that internal theological concerns in the seventeenth and eighteenth century gave rise to a specific conceptual language used in thinking about and discussing paganism. This language was later adopted by contemporary Pagans in the twentieth and twenty first century. As such, the article argues, in any study of the phenomenon referred to as "paganism" the present framework inevitably leads one to theological questions and answers. As a result, while the discussion on paganism continues to be a theological one, the phenomenon being studied remains inaccessible.